(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate personality characteristics of authors of sexual violence against children and adolescents. Methodology: Four male individuals, aged between 41 and 63, condemned for intrafamily sex crime participated in the study, prisoners in a state prison, located to the northwest of the state of Rio Grande do Sul. Instruments: Sociodemographic record, Factorial Personality Inventory (IFP-II), Neupsilin, Zulliger Method and Thematic Apperception Test (TAT). Results: Personality traits indicated a search for personal affirmation, power and control over others, difficulties in dealing with impulses, desires to dominate and seduce, vulnerability with regard to internal aspects, as well as distorted perception of reality and lack of social skills. Final Considerations: The ideographic findings are compatible with the literature and can be useful to support psychological evaluations and intervention measures, as well as instigating follow-up studies.